COPING PATTERNS OF WOMEN BREAST CANCER SURVIVORS IN KIGALI-RWANDA A PHENOMENOLOGICAL STUDY - ASEMOTA, Olukemi Olufunmilola; Rwanda, Kigali (IJRDO - Journal of Business Management, 2015)
Breast cancer is one of the leading causes of cancer deaths amongst women worldwide. Most women diagnosed with breast cancer live throughout life with some challenges and thereby adopt some coping mechanisms in order to minimise their ordeal. This study examined the coping patterns exhibited by Women Breast Cancer Survivors (WBCS). A phenomenological research design was employed with the snow ball approach for data collection. Ten (10) WBCS were interviewed with average age of 40 years. The results show that WBCS shared common four coping patterns, namely: spirituality, support from family and friends, the medical team, the use of prosthesis. Other emerged sub themes were: disease removal not organ removal, and socialising with other victims of breast cancer. The results showed that women who survived breast cancer always have a story to tell on their coping patterns despite the debilitating physical and emotional traumas of living with breast cancer.